2023
DOI: 10.3389/fimmu.2023.1144813
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cervical lymphatic immunotherapy for dust mite-induced allergic rhinoconjunctivitis in children: a 3-year prospective randomized controlled trial

Abstract: BackgroundPediatric allergic rhinoconjunctivitis has become a public concern with an increasing incidence year by year. Conventional subcutaneous immunotherapy (SCIT) has long treatment time, high cost and poor compliance. The novel immunotherapy significantly shortens the course of treatment by directly injecting allergens into cervical lymph nodes, which can perform faster clinical benefits to children.ObjectiveBy comparing with SCIT, this study aimed to evaluate the long-term efficacy and safety of intra-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Successful AIT elicits allergen‐specific B cell responses with the help of T cells or alone, producing antibody isotypes derived from B cells, such as IgA, IgG, and IgE, consequently sustaining an allergen‐specific immune tolerance 19 . The ICLIT has been demonstrated as a novel, effective treatment through the evaluation of clinical outcomes and total quality of life score with an advantage in efficacy, safety, and patient adherence 15 . Even though the underlying molecular mechanism of AIT has not been fully illustrated, the perspective from immunologists insisted that the induction of immunological tolerance to allergens regulated by allergen‐specific IgE and protective IgG4 as well as IgA play a crucial role in the procedure of AIT 7,11,20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Successful AIT elicits allergen‐specific B cell responses with the help of T cells or alone, producing antibody isotypes derived from B cells, such as IgA, IgG, and IgE, consequently sustaining an allergen‐specific immune tolerance 19 . The ICLIT has been demonstrated as a novel, effective treatment through the evaluation of clinical outcomes and total quality of life score with an advantage in efficacy, safety, and patient adherence 15 . Even though the underlying molecular mechanism of AIT has not been fully illustrated, the perspective from immunologists insisted that the induction of immunological tolerance to allergens regulated by allergen‐specific IgE and protective IgG4 as well as IgA play a crucial role in the procedure of AIT 7,11,20 .…”
Section: Discussionmentioning
confidence: 99%
“…19 The ICLIT has been demonstrated as a novel, effective treatment through the evaluation of clinical outcomes and total quality of life score with an advantage in efficacy, safety, and patient adherence. 15 Even though the underlying molecular mechanism of AIT has not been fully illustrated, the perspective from immunologists insisted that the induction of immunological tolerance to allergens regulated by allergen-specific IgE and protective IgG4 as well as IgA play a crucial role in the procedure of AIT. 7,11,20 We herein investigated the primary B cell populations in peripheral blood from an AR patient who underwent ICLIT, using scRNA-seq to unveil the AIT-related phenotype with the transcriptome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trial demonstrated that ILIT significantly improved both symptoms and quality of life, reduced administration of rescue medication, and no moderate or severe adverse events. Another prospective randomized controlled trial, spanning over 3 years, assessed the long-term efficacy and safety of cervical ILIT in 50 children with HDM-induced allergic rhino-conjunctivitis ( 164 ). The trial showed that compared with SCIT, cervical ILIT could improve allergic symptoms more rapidly, shorten the period of treatment, and lower pain perception.…”
Section: Modified Regimen and Novel Routes Of Administration Of Aitmentioning
confidence: 99%